Repercussions of singularity of site authorities in making heritage conservation decisions: evidence from Iraq - Jasim, Mohammed Awadh; Hanks, Laura; Borsi, Katharina (Tongji University Press, 2018)
Different global assertions have recently been made prohibiting the mono approach of decision-makers in formulating heritage conservation policies, due to many unfavourable touristic and political implications. The mono approach has led to exploitation of some sites’ cultural standing as well as condoning a veritable remedy of some of their social and urban aspects, and thus threatening these sites with exclusion from the World Heritage List. This paper investigates the approach of some local Iraqi experiences of conservation, aiming at revealing some of the more painful repercussions of the singularity of site authorities in planning for built heritage future, which may draw a plan for the site away from its heritage potential. Some local cases are reviewed here, such as Erbil Citadel, setting them as examples that may add more facts to the global experience of heritage conservation in this regard. The paper concludes that the site authorities are also liable to drift as a result of some ramifications that impede setting a deep-sighted strategy, and thus may stray far from delivering the far-reaching aims. Accordingly, the monaural authority approach may need to be synthesised with some of the site’s locally-based views through an overlapped integral loop of interactions between them, which may support the conservation policy-formulation with diverse contributions.